Prognostic value of the triglyceride—glucose index in non-muscle-invasive bladder cancer: a retrospective study - Zhang, Yan; Shao, Xianfeng; Ding, Li; Xia, Wentao; Wang, Kun; Jiang, Shan; Wang, Jiahao; Wang, Junqi (Frontiers in Nutrition, 2024)
BackgroundBladder carcinoma is a type of urological tumor with high risks of recurrence and progression. The triglyceride-glucose (TyG) index has demonstrated significant promise as a prognostic marker for metabolic health in different types of cancer. Further research is needed to explore the relationships among non-muscle-invasive bladder cancer (NMIBC), the TyG index, and its prognostic importance. Purpose of this preliminary research is to assess the predictive significance of the TyG index for recurrence and progression risk in NMIBC patients.MethodsData from patients admitted between October 2018 and July 2021 were reviewed, and there are 198 patients in total were included. The experimental data were supplied by medical records. In addition, patient prognoses were followed up via telephone. Furthermore, patients were separated into two groups: the high and low TyG groups, using X-tile software. Apart from recurrence-free survival (RFS), progression-free survival (PFS) was the main outcome. According to the TyG index, nomograms were also established.ResultsThe cohort consisted of 93 patients in the high TyG group and 105 patients in the low TyG group. The TyG index was a key prognostic factor for postoperative RFS (HR = 2.726, 95% CI = 1.474–5.041, p = 0.001) and PFS (HR = 2.846, 95% CI = 1.359–5.957, p = 0.006) among patients with NMIBC. The log-rank test revealed a notable disparity between the low and high TyG groups regarding RFS (p = 0.0025) and PFS (p = 0.0110). Moreover, it was strongly connected to well-known NMIBC risk factors. Because the TyG index exhibited good predictive value, the nomogram models were formulated.ConclusionThe TyG index serves as an isolated predictor of both RFS and PFS among patients with NMIBC, revealing new insights into disease treatment mechanisms. Indeed, the TyG index serves as a credible indicator of risk classification while facilitating early intervention among patients with NMIBC.